Efektivitas Pelaksanaan PERDA Pengelolaan Sampah di Batam Kota Terhadap Sustainable Development Goals - Yan Alriyadi; Nurlaily Nurlaily; Triana Dewi Seroja (LPPM Universitas Ekasakti Padang, 2023)
Waste management is something that is important and needs attention. The 1945 Constitution has guaranteed the basic rights of citizens to the environment as stipulated in Article 28H paragraph (1) of the 1945 Constitution which reads